New directions in male-tailored psychotherapy for depression - Eggenberger, Lukas; Ehlert, Ulrike; Walther, Andreas (Frontiers in Psychology, 2023)
Purpose of review Societal, cultural, and contextual norms about how men should be and behave (so called traditional masculinity ideologies; TMI) affect men’s presentation of depressive disorders, psychotherapy use, and treatment engagement. Only recently, however, male-tailored psychotherapy approaches for depressive disorders have been developed, which aim to systematically soften dysfunctional TMI. In this review, we outline the necessary groundwork as well as recent advances in research on TMI, men’s help-seeking, male depression, and their interrelatedness. Subsequently, we discuss the potential value of these findings for male-tailored psychotherapy for depressive disorders. Recent findings A preliminary evaluation of a male-specific psychoeducation program found that a male-specific psychoeducation text could reduce negative affect as well as state shame and potentially elicit a shift from externalizing depression symptoms toward more prototypical depression symptoms. The James’ Place program, a male-tailored community-based service, improved suicidal men’s overall well-being, problems, functioning, and suicide risk. The Heads Up Guys! program, an eHealth resource aimed at depressed men, reported a high and increasing global interest in their website, with considerable visitor engagement. The Man Therapy online resource improved depressive symptoms, suicidal ideation, and help-seeking behavior. Finally, the Men in Mind program, an online training program for clinical practitioners, increased practitioners’ capacity to engage and support men in therapy. Summary Male-tailored psychotherapy programs for depressive disorders, which are informed by recent advances in TMI research, may potentially increase therapeutic effectiveness, engagement, and adherence. While recent preliminary analyses of individual male-tailored treatment programs show promising results, extensive and systematic primary studies evaluating these programs are pending but greatly needed.